Bloating and Abdominal Distension: Clinical Approach and Management - Mari, Amir (Adv Ther, 2019)
Functional abdominal bloating and distension (FABD) are common gastrointestinal complaints, encountered on a daily basis by gastroenterologists and healthcare providers. Functional abdominal bloating is a subjective sensation that is commonly associated with an objective abdominal distension. FABD may be diagnosed as a single entity (the sole or cardinal complaint) or may overlap with other functional gastrointestinal disorders such as functional constipation, irritable bowel syndrome, and functional dyspepsia. The pathophysiology of FABD is not completely understood. Proposed underlying mechanisms include visceral hypersensitivity, behavioral induced abnormal abdominal wall-phrenic reflexes, the effect of poorly absorbed fermentable carbohydrates, and microbiome alterations. Management includes behavioral therapy, dietary interventions, microbiome modulation, and medical therapy. This review presents the current knowledge on the pathophysiology, evaluation, and management of FABD.